Romanesque and the year 1000
1 online resource.
Keywords: "Romanesque and the Year 1000 examines the art and architecture of the Latin West between c.970 and c.1030, a period which witnessed crucial developments in iconography and stylistic expression across a wide range of media. Despite the complex political situation in late-10th-century Europe - a period marked by chaos in some areas and the effective exercise of authority in others - the last quarter of the century saw an apparent upsurge in artistic production in the Empire, southern Britain, Lombardy, the Alps and Mediterranean, albeit one whose survival rate is low. The decades after the millennium have left a larger residue of work, notably in France, Catalonia and northern Italy, but were the 1020s artistically more dynamic than the 980s? How might we describe the cultural climate of the Latin West between c.970 and c.1030? Individual chapters examine the influence of Carolingian art on artistic production around 1000, the emergence of new approaches to architecture in France, Germany, England and northern Italy, and the response of artists to perceived order and disorder at the turn of the millennium. There are studies of architectural sculpture in Catalonia and Castile, new town foundation in Saxony, and monastic architecture in southern Britain, together with examinations of Ottonian sarcophagi, book covers in gold and ivory, the wall paintings at Reichenau, the patronage of Willigis at Mainz and Robert the Pious in northern France, the early Romanesque of Poland and Hungary and the reflection of a new type of affective piety in the manuscript illumination of late Anglo-Saxon England. Romanesque and the Year 1000 presents a wealth of new research into artistic production at a critical period and is of interest to art historians, archaeologists and historians alike"--